The The Effect Of Population And Macroeconomic Indicators On Economic Growth In OIC Countries - Habibullah, Habibullah (Jurnal Ekonomi, 2024)
This study examines the impact of population growth and macroeconomic conditions on economic growth in the five most populous OIC member states: Bangladesh, Pakistan, Egypt, Indonesia, and Nigeria. Utilizing data spanning 2000 to 2022 from the World Bank and official State Bureaus of Statistics, a random effects model is employed to analyze these relationships. The primary objective is to evaluate the effects of population growth, foreign direct investment (FDI), consumption expenditure, export growth, inflation, and exchange rates on economic growth. The results indicate that population growth and inflation do not have statistically significant negative impacts on economic growth. In contrast, FDI, consumption expenditure, and export growth exhibit significant positive effects, whereas the exchange rate does not demonstrate a significant positive effect. These findings contribute to a deeper understanding of the intricate dynamics among these variables and provide essential insights for the formulation of evidence-based policies aimed at fostering sustainable economic development. By concentrating on the most populous OIC member states and utilizing recent data, this study offers timely and relevant contributions to economic analysis and policy formulation.